1996
DOI: 10.1136/hrt.75.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Salt supplement increases plasma volume and orthostatic tolerance in patients with unexplained syncope.

Abstract: Objective-To determine whether in patients presenting with posturally related syncope administration of salt increases plasma volume and improves orthostatic tolerance. Patients with poor tolerance of orthostatic stress tend to have lower than average plasma and blood volumes. Design-A double blind placebo controlled study in 20 patients and an open study in 11 of the effects of giving 120 mmoUday of sodium chloride. Patients-31 patients presenting with episodes of syncope who had no apparent cardiac or neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
166
3
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(174 citation statements)
references
References 17 publications
2
166
3
3
Order By: Relevance
“…6,71 Similarly, expansion of plasma volume following salt supplementation improves orthostatic tolerance. 72,73 Thus, it would be expected that salt depletion and/or small plasma volumes would predispose to orthostatic hypotension. 66 In patients with chronic SCI, there is evidence of impaired water and sodium retention in the seated position, and limited salt and water intake.…”
Section: Altered Salt and Water Balancementioning
confidence: 99%
“…6,71 Similarly, expansion of plasma volume following salt supplementation improves orthostatic tolerance. 72,73 Thus, it would be expected that salt depletion and/or small plasma volumes would predispose to orthostatic hypotension. 66 In patients with chronic SCI, there is evidence of impaired water and sodium retention in the seated position, and limited salt and water intake.…”
Section: Altered Salt and Water Balancementioning
confidence: 99%
“…Changes of this magnitude in patients with attacks of syncope or presyncope are associated with considerable symptomatic improvements. 19 Subjects with lower orthostatic tolerance had the greatest improvement in orthostatic tolerance. In an earlier study, cardiovascular and hematologic responses to tilt testing were examined after 26 hours of dehydration and after oral rehydration.…”
Section: Schroeder Et Al Water Drinking and Orthostatic Tolerancementioning
confidence: 99%
“…We have developed a sensitive and reproducible measure of orthostatic tolerance which determines the time to onset of presyncope in a progressive test of head-up tilt combined with lower body suction . This test is able to distinguish results from patients with unexplained syncope from those from normal controls and has been used to assess possible benefits of therapeutic interventions El-Sayed & Hainsworth, 1996).…”
Section: B L M T L N a N G L A N D R H A I N S W O R T Hmentioning
confidence: 99%
“…We have reported that orthostatic tolerance is significantly correlated with plasma and blood volumes (El-Sayed & Hainsworth, 1995) and that, if these can be expanded by salt loading, orthostatic tolerance improves (El-Sayed & Hainsworth, 1996). Since exercise training is also known to increase plasma and blood volumes (Saltin et al 1968), if all other things are equal, orthostatic tolerance should also improve.…”
Section: Introductionmentioning
confidence: 99%